2023
DOI: 10.1021/acs.bioconjchem.3c00347
|View full text |Cite
|
Sign up to set email alerts
|

Self-Adjuvanting TLR7/8 Agonist and Fentanyl Hapten Co-Conjugate Achieves Enhanced Protection against Fentanyl Challenge

Noah Powers,
Casey Massena,
Bethany Crouse
et al.

Abstract: Currently approved pharmacotherapies for opioid use disorders (OUDs) and overdose reversal agents are insufficient to slow the spread of OUDs due to the proliferation of fentanyl. This is evident in the 31% rise in drug overdose deaths from 2019 to 2022, with rates increasing from 21.6 to 28.3 overdoses per 100,000 deaths. Vaccines are a potential alternative or adjunct therapy for the treatment of several substance use disorders (nicotine, cocaine) but have shown limited clinical success due to suboptimal ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…It is conceivable that boosting the efficacy of each individual vaccine could enable concurrent protection against higher drug doses or more complex drug mixtures. Incorporating TLR agonists into the vaccine formulation, for example, has been shown to increase the efficacy of conjugate vaccines. ,,, …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is conceivable that boosting the efficacy of each individual vaccine could enable concurrent protection against higher drug doses or more complex drug mixtures. Incorporating TLR agonists into the vaccine formulation, for example, has been shown to increase the efficacy of conjugate vaccines. ,,, …”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies identified lead haptens designed to target fentanyl (F), carfentanil (Carf), oxycodone (Oxy), and heroin/morphine (M), whose individual lead candidate conjugate vaccines (F-CRM, Carf-CRM, Oxy-sKLH, and M-sKLH, respectively) were effective in blocking the distribution of their respective target drug to the brain and reducing their behavioral effects in mice, rats, , and mini-pigs . Among these conjugate vaccines, a vaccine against oxycodone (Oxy-sKLH) is currently in Phase I clinical trials (NCT04458545), while the other lead conjugate vaccines F-CRM and M-sKLH are either in the process of being manufactured or readied for upcoming clinical trials, which will include the incorporation of toll-like receptor (TLR) 7/8 agonists to enhance efficacy. ,, Throughout the remainder of this paper, the M hapten and its conjugated form, M-sKLH, will be referred to as “Her” and “Her-sKLH”, respectively, as they target heroin, 6-acetylmorphine (6-MAM), and morphine …”
mentioning
confidence: 99%